Change management reduces antibiotic use on pig farms. Issue 7 (25th June 2019) - McKenzie, P; Carter, R
Abstract : A clostridial 'syndrome' in suckling and weaner pigs, with risk factors of high injectable ceftiofur use and poor hygiene, presented an opportunity to engage in management change to improve pig health and reduce ceftiofur use on four farms. Management changes included all‐in‐all‐out pig flow, batch disinfection with biofilm control, reduced protein starter diets, appropriate stocking density and the use of an anti‐clostridial probiotic. Assessment of the program was obtained from a questionnaire. The health and production changes were positive across all farms and were associated with reduced use of antibiotics, together with cost and labour savings. Provided there is a good relationship between a committed, competent veterinarian, and a committed, competent manager, change management programs can be successfully implemented over 6–12 months.